K(+) versus Na(+) ions in a K channel selectivity filter: a simulation study. - Shrivastava, I; Tieleman, D; Biggin, P; Sansom, MS (2002)
Molecular dynamics simulations of a bacterial potassium channel (KcsA) embedded in a phospholipid bilayer reveal significant differences in interactions of the selectivity filter with K(+) compared with Na(+) ions. K(+) ions and water molecules within the filter undergo concerted single-file motion in which they translocate between adjacent sites within the filter on a nanosecond timescale. In contrast, Na(+) ions remain bound to sites within the filter and do not exhibit translocation on a nanosecond timescale. Furthermore, entry of a K(+) ion into the filter from the extracellular mouth is observed, whereas this does not occur for a Na(+) ion. Whereas K(+) ions prefer to sit within a cage of eight oxygen atoms of the filter, Na(+) ions prefer to interact with a ring of four oxygen atoms plus two water molecules. These differences in interactions in the selectivity filter may contribute to the selectivity of KcsA for K(+) ions (in addition to the differences in dehydration energy between K(+) and Na(+)) and the block of KcsA by internal Na(+) ions. In our simulations the selectivity filter exhibits significant flexibility in response to changes in ion/protein interactions, with a somewhat greater distortion induced by Na(+) than by K(+) ions.